Traces of Time in the History of Editing the Book of Lithuanian Folk Songs - Stundžienė, Bronė (Tautosakos darbai, 2021)
The 40th anniversary of publication of the Book of Lithuanian Folk Songs (1980–2020), with its 25th volume being published, presents a good opportunity to look back into the history of this significant long-time project. Already during the interwar period, the leading Lithuanian scholars of literature and folklore proposed an idea of launching a multi-volume edition of the rich Lithuanian folksong heritage, comprising hundreds of thousands of variants accumulated in the archives or printed sources. This idea was successfully implemented much later. The publication of the collection of Lithuanian songs started only in 1980, in the late Soviet period, and has continued ever since – through restoration of Lithuanian independence in 1990 and until nowadays. The history of this huge folksong project is particularly impressive in terms of the time span of its implementation, meriting a separate study. The current article focuses on the role of time in the process of publishing the Book of Lithuanian Folk Songs that embraced two entirely different political epochs (the first five volumes saw publication in Soviet times). Such angle of investigation was prompted by the particularly strict ideological censorship that was applied during Soviet period to all publications, especially those belonging to the sphere of humanities, including fiction and research. The current research is methodologically supported by quite advanced studies of the Soviet period carried out by the Lithuanian historians and literary scholars, and among other things encompassing the complicated and watchful surveillance of press, the censors being enabled to judge whether or not a given publication suited the ideological requirements and therefore could or could not be published. The author presents a brief overview of the experiences gained by the editors of the Book of Lithuanian Folk Songs and some previous folklore publications that testify to their growing “skills” in substantiating the proposed publications in order to get them to see the daylight, and to save them from being banned by politically faultfinding Soviet censors. Certain circumstances that facilitated folklore research and publication are also discussed. These primarily include the “folk” character of the material in question, relating it to the Marxist definition of the suppressed and exploited class – namely, the peasants. In Soviet period, this endowed folklore with certain privileges unavailable to literature, for instance. The main part of the research presented in the current article essentially focuses on two issues: 1) the development of the ideologically constrained public spread of folklore, primarily folksongs that were scrupulously surveyed by the Soviet censors; 2) changes and continuity in the publication concept of the Book of Lithuanian Folk Songs after Lithuania regained independence. The author concludes that typological, or genre-related structural pattern of the collection was not essentially updated under the impact of the same – time factor; however, not only Soviet in this case. Certain stagnation possibly resulted due to the unchanged research methodology of the Lithuanian folksongs that was applied since the very first publications and persisted in the course of the whole 20th century, mainly centering on the artistic qualities of the folklore expressions.
Keywords: Book of Lithuanian Folk Songs; editing; concept; Soviet period; ideological censorship; the present; signs of change